Efficient Preconstruction of Three-Dimensional Graphene Networks for Thermally Conductive Polymer Composites - Zhao, Hao‑Yu; Yu, Ming‑Yuan; Liu, Ji; Li, Xiaofeng; Min, Peng; Yu, Zhong‑Zhen (Nano-Micro Letters, 2022)
Electronic devices generate heat during operation and require efficient thermal management to extend the lifetime and prevent performance degradation. Featured by its exceptional thermal conductivity, graphene is an ideal functional filler for fabricating thermally conductive polymer composites to provide efficient thermal management. Extensive studies have been focusing on constructing graphene networks in polymer composites to achieve high thermal conductivities. Compared with conventional composite fabrications by directly mixing graphene with polymers, preconstruction of three-dimensional graphene networks followed by backfilling polymers represents a promising way to produce composites with higher performances, enabling high manufacturing flexibility and controllability. In this review, we first summarize the factors that affect thermal conductivity of graphene composites and strategies for fabricating highly thermally conductive graphene/polymer composites. Subsequently, we give the reasoning behind using preconstructed three-dimensional graphene networks for fabricating thermally conductive polymer composites and highlight their potential applications. Finally, our insight into the existing bottlenecks and opportunities is provided for developing preconstructed porous architectures of graphene and their thermally conductive composites. Highlights: 1 Fundamental principles for designing high-performance thermally conductive graphene-based polymer composites are reviewed in detail. 2 The reasoning behind using the preconstructed graphene 3D networks for fabricating thermally conductive composites and recent progress are discussed in-depth. 3 Insight into the existing bottlenecks and opportunities in developing preconstructed 3D networks of graphene and their thermally conductive composites is also presented.